“Métodos de la aplicación del abono líquido en plantones de palma aceitera (elaeis guineensis jacq) en valle de shanusi-Loreto” - Pisco Salas, Carlos Humberto (2014)
This research work entitled "Methods of liquid manure application in seedlings of oíl palm (Elaeís guineensis Jacq) in Valley Shanusi - Loreto", was conducted in order to evaluate three methods of applying liquid fertilizer (Avibiol) and determine the most appropriate method for the production of seedlings in the nursery phase. Design Randomized Complete Block (RCBD) with five treatments and three replications. Emergence percentage, plant height (cm), stem diameter / plant (cm), number of leaves / plant, coefficient of determination, correlation coefficient, and regression in the number of leaves per plant, plant height was evaluated and stem diameter. The results indicate that the T4 (T1 = Application by dipping seeds, T2 = soil application (Oreen ch) and T3 = foliar application ), the best method of treatment application was obtained in most of the evatuated variables and the better resutts in terms of unit time. We conclude that Avibiol Manure is a great interest in the benefits and be reflected economic and environmental interest, under the conditions Shanusi Valley in Loreto. Keywords: methods, fertilizer application, liquid, plants, oil, economic, environmental palm